'It's a tough decision': a qualitative study of proxy decision-making for research involving adults who lack capacity to consent in UK. (9th October 2019) - Shepherd, Victoria; Hood, Kerenza; Sheehan, Mark; Griffith, Richard; Wood, Fiona
Abstract: Background: Research into dementia and other conditions connected with cognitive impairments is essential but conducting research with populations who lack capacity to provide consent involves a number of ethical, legal and practical challenges. In England and Wales, family members can act as a consultee or legal representative on behalf of someone who lacks capacity. However, there is a paucity of research about how family members make decisions concerning research participation. Objective: To explore family members' experiences of proxy decision-making for research. Understanding how proxy decisions are made could lead to interventions to support greater inclusion of individuals in research who have impaired decision-making capacity. Methods: Semi-structured interviews were conducted with a purposive sample of 17 family members who had experience as a proxy for making decisions about participation in research, including those who had agreed to participation and those who declined. Thematic analysis was used to examine experiences and generate findings for research practice and to develop future supportive interventions. Results: Proxy decision-making is highly contextualised. Proxies balance a number of factors when deciding about research participation, including the person's values and preferences, within the specific context of the study, and the practicalities of being involved. Proxies use these factors to construct a decision that is authentic to the person they care for. Conclusions: Proxy decision-making for research is a complex process with inter-woven layers of decision-making. Decisions can be problematic for some proxies who may benefit from decision support to make an informed decision about research participation on behalf of a family member.